2020
DOI: 10.1016/j.physletb.2020.135317
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Planckian censorship and inflation in grand unified theories

Abstract: The recently proposed trans-Planckian censorship conjecture (TCC) amounts to the claim that inflation models with an inflationary energy scale larger than Λ max inf ∼ 10 9 GeV belong to the swampland, i.e., cannot be embedded into a consistent theory of quantum gravity. In this paper, we point out that this constraint can be readily satisfied in D-term hybrid inflation (DHI), which is a well-motivated inflation scenario in the context of supersymmetric grand unification. In DHI, the amplitude of the primordial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 138 publications
(225 reference statements)
0
10
0
Order By: Relevance
“…In [5] it was shown that the simplest TCC-compatible potential that could fit the observations such as the CMB power spectrum is an inverted parabola. A similar hilltop model was discussed in [36]. A concrete example of this can be taken to…”
Section: Inflationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5] it was shown that the simplest TCC-compatible potential that could fit the observations such as the CMB power spectrum is an inverted parabola. A similar hilltop model was discussed in [36]. A concrete example of this can be taken to…”
Section: Inflationmentioning
confidence: 99%
“…In [5] it was shown that the simplest TCC‐compatible potential that could fit the observations such as the CMB power spectrum is an inverted parabola. A similar hilltop model was discussed in [36]. A concrete example of this can be taken to be V=V0false(10.02ϕ2false) defined over [ϕi,ϕf] where ϕf is fixed by observation to be truerightϕf3.9×105·V0Mpl0.505.Plugging this into the potential gives trueright|V|(ϕf)8×1030.16emV01.505.For small enough V 0 and large enough ϕi the above potential is consistent with the no‐eternal inflation condition as well as the TCC.…”
Section: Cosmological Implicationsmentioning
confidence: 99%
“…This restricts the energy scale of a phase of inflation to be fairly low, hence placing a bound on the tensor-to-scalar ratio of r < O(10 −30 ), as shown in [16]. Even though there are models that satisfy this constraint [18][19][20][21], it has been also pointed out that the bound is less demanding for bouncing cosmologies and other pre-inflationary scenarios, basically for the same reasons that they are less sensitive to the TP problem [16,22]. Along those lines, other scenarios like a multi-stage inflation [23], excited initial states [24] or non-standard expansion histories [25,26] can also mitigate the TCC constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, there are models that are compatible with these criteria, but they are always associated with the problems in the initial conditions which has been extensively discussed in Refs. [45] and [46]. The objective of this paper is to improve the aforementioned situation.…”
Section: Introductionmentioning
confidence: 99%